THE UNSEEN DATA: A STATISTICAL AND ENGINEERING PERSPECTIVE ON BIASES IN LARGE LANGUAGE MODELS - Туманов, Олексій (SWorldJournal, 2025)
The paper argues that bias in large language models (LLMs) is a fundamentally statistical problem rooted in the nature of their training data. The unfiltered datasets used for training are not representative samples of human language, but rather deeply im